Strong coupling expansion of the entanglement entropy of Yang-Mills gauge theories - Jiunn-Wei Chen (Nuclear Physics B, 2020)
We propose a novel prescription for calculating the entanglement entropy of the SU(N) Yang-Mills gauge theories on the lattice under the strong coupling expansion in powers of β=2N/g2, where g is the coupling constant. Using the replica method, our Lagrangian formalism maintains gauge invariance on the lattice. At O(β2) and O(β3), the entanglement entropy is solely contributed by the central plaquettes enclosing the conical singularity of the n-sheeted Riemann surface. The area law emerges naturally to the highest order O(β3) of our calculation. The leading O(β) term is negative, which could in principle be canceled by taking into account the “cosmological constant” living in interface of the two entangled subregions. This unknown cosmological constant resembles the ambiguity of edge modes in the Hamiltonian formalism. We further speculate this unknown cosmological constant can show up in the entanglement entropy of scalar and spinor field theories as well. Furthermore, it could play the role of a counterterm to absorb the ultraviolet divergence of entanglement entropy and make entanglement entropy a finite physical quantity.